Cu–Cu hermetic seal enhancement using self-assembled monolayer passivation - Peng, L. (2013)
Low-temperature Cu–Cu thermocompression bonding enabled by self-assembled monolayer (SAM) passivation for hermetic sealing application is investigated in this work. Cavities are etched to a volume of 1.4 × 10−3 cm3 in accordance with the MIL-STD-883E standard prescribed for microelectronics packaging. The wafer pairs (nonfunctional cavity wafer and cap wafer) are annealed and bonded at 250°C under a bonding force of 5500 N. The encapsulated cavities undergo helium overpressure in a bombing chamber, and the helium leak rate is detected by a mass spectrometer. The measurement results show that the cavities sealed with Cu–Cu bonding after SAM passivation exhibit excellent hermeticity with a leak rate below 10−9 atm cm3/s, which is an improvement of at least 2× compared with the control sample without SAM passivation.